Women's employment, segregation and skills in the future of work. (2nd January 2019) - Peetz, David; Murray, Georgina
ABSTRACT: Discussion of the future of work has focused a lot on the type or number of jobs that new technology will create or destroy. Little consideration has been given to how gender fits into that. This article examines this by considering: (a) the automatability of male and female jobs; (b) employment projections for male and female jobs; (c) past and projected sex segregation of employment; and (d) past and projected skill levels of male and female jobs. Our analysis makes use of historical data and projections for the Australian and US labour markets. It appears that neither technological change nor other structural changes in labour markets are likely to especially disadvantage women. If anything, women's jobs are slightly more secure (or less insecure) than men's; there has been, and will be, an improvement in the skill levels of jobs held by women; and there has been a small reduction in average sex segregation. However, developments within specific industries are important and difficult to predict. In that respect, the information and communications technology (ICT) occupations go against the trend elsewhere, having experienced transformation in their gender composition that is reinforcing, rather than weakening, gender segmentation.